Can current Indian health system achieve health related SDG's? - Suresh Kishanrao (Open Journal of Pediatrics and Child Health - Peertechz Publications, 2019)
Introduction: India has committed to Sustainable Development Goals and Universal Health Coverage by 2030. National Health Policy 2017 is in place with a Goal of The attainment of the highest possible level of good health and well-being, through a preventive and promotive health care orientation in all developmental policies, and universal access to good quality health care services without anyone having to face fi nancial hardship as a consequence. However, the health care system in the country suffers from inadequate funding. There are several structural problems too, like the lack of integration between Disease control, Family Welfare Programs, non- communicable diseases control and other programmes in the social sectors. Over the years differential priorities for interventions have led to poor accountability for Results of Primary Health Care and recent commitment of Universal Health Care.